Education as a political act in Freire. Anti-dialogical theory, cultural arbitrariness and banking education: notions to understand the reproduction of inequalities in Latin America - García Fernández, Raúl; García Marín, Anthony (Innovaciones Educativas, 2022)
The essay proposes a discussion to understand education as a political act, from the notions about social inequality that are implicit in the first phase of Freire's work. For this, it starts from the understanding of the educational, the social and the conflict in the oppressed subject-oppressor subject relationship. Likewise, the centrality that notions such as the dialogical versus the anti-dialogical acquire in it, the link between objectivity and subjectivity, the processes of awareness and praxis, that is, the joint relationship of action and critical reflection; all this within the framework of liberating education. One of the premises of the essay is that in Freire's work there is no explicit mention of what is currently known as the "social inequality" approach, but rather that it is assumed in the vast Freirean discussion. It is argued that, through anti-dialogical relations, the definition of cultural arbitrary and banking education, the oppressive subjects guarantee the maintenance of the material and symbolic conditions of oppression. In other words, it is above all about inequalities of knowledge, the product of an education that does not allow the process of humanization and awareness for the liberation of the oppressed.